Study of Terms and Standards of Application of Liquid Nitrogen Fertilizers in Cotton Farming - Tukhtashev Farrukhjon Esonali ugli (Web of Journals Publishing, 2023)
This article examines the effects of foliar feeding of cotton with liquid nitrogen fertilizers on the growth and development of cotton. Physiologically active substances play a very important role in the care of crops in agriculture, in increasing seed germination and germination capacity, in improving plant growth and development, in increasing resistance to drought, salt, disease and pests. they have a positive effect on the plant.
Keywords: cotton, cotton, fertilizer, harvest elements, product horn, cotton, complex fertilizer, mineral fertilizers, nitrogenous fertilizers, productivity, suspension, number of flowers.